2022
DOI: 10.3390/ijerph19158905
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine Uses for Respiratory System Disorders and Possible Trends in New Herbal Medicinal Recipes during COVID-19 in Pasvalys District, Lithuania

Abstract: Despite some preliminary studies of the available herbal medicine preparations and their curative effects on COVID-19, experts still fear that unproper use of such homemade medicines could do more harm than good to people relying on unproven alternatives of questionable efficacy. The main purpose of this study was to evaluate the safety of herbal medicines used for respiratory system disorders in the Pasvalys district during the COVID-19 pandemic in Lithuania. An archival source was also studied, looking for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…In the study conducted in Lithuania on medicinal plant use the authors reported that the percentage of men and women was unequal because traditionally, knowledge of herbal medicine in the country is passed down through the female line and even today, herbalists are usually women (Pranskuniene et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted in Lithuania on medicinal plant use the authors reported that the percentage of men and women was unequal because traditionally, knowledge of herbal medicine in the country is passed down through the female line and even today, herbalists are usually women (Pranskuniene et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the methodology of others was to investigate the use of medicinal plants by participants who did not have a diagnosis of COVID-19, and the results showed that many people used the plants to treat the symptoms of the disease, based on prior knowledge passed down from generation to generation for viral diseases that had similar symptomatology (Pranskuniene et al, 2022, Villena-Tejada et al,2020, Khadka et al, 2021.…”
Section: The Medicinal Plants For Covid-19 Treatments: An Integrative...mentioning
confidence: 99%
“…On the other hand, some of these metabolites have important effects at the cellular and physiological level in the human organism, owing to their therapeutic properties. They have effects on different diseases, including respiratory diseases, neurodegenerative diseases, cardiovascular diseases, diabetes, obesity, among others [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…They mainly include chronic obstructive pulmonary disease (COPD), asthma, pneumonia, pulmonary fibrosis, lung cancer, and, more recently, SARS-CoV-2 (COVID-19). Most of the population suffers from some respiratory disease at least once a year [ 19 , 24 ]. In 2019, the entire world was affected by the SARS-CoV-2, a virus that affects the respiratory system and caused the death of millions of people during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation